Use of Circulation Statistics in Collection Management: A Case Study of Hacettepe University - Al, Umut; Soydal, İrem (Information World, 2011)
In this study, Hacettepe University Libraries, which provide services for various types of faculties having one of the largest book collections in Turkey, were investigated in terms of their book collection. The aim of the study is to help the decision makers to understand their own collection in a better way, to support the decision making process for selecting new materials or weeding existing ones in the light of circulation statistics. In this context, the most frequently requested books by Hacettepe University Libraries’ users were determined and the collection analysis was built on the circulation statistics. The usage differences among the subject fields based on Library of Congress (LC) classes were also examined in this study by analyzing the circulation statistics. Findings showed that there was almost seven‐fold difference between the average number of total circulation in the classes of Language & Literature and Fine Arts.
Keywords: Collection management; Circulation statistics; Usage analysis; Usage statistics